Farmer Corporation Management in Agroforestry Activities to Support Food Security - Dewanto, Heru; Sarjito, Aris; Duarte, Editya Praditya; Purwantoro, Susilo Adi (International Journal of Business, Law, and Education, 2025)
This study aims to analyze the role of farmer corporate governance in agroforestry activities and its implications for strengthening food security in Indonesia. Data collection techniques included literature studies from books, national journals, articles, and previous theses related to this research. The results indicate a synergistic relationship between farmer corporate governance and agroforestry success. A strong relationship is believed to enhance cooperation, strengthen interactions, reduce transaction costs, and guarantee a stable market. Corporate governance fosters organized management, including the development of partnerships between farmers and downstream industries, thereby encouraging better market access and strengthening the bargaining position of agroforestry farmers. Well-managed farmer corporations typically include technical and managerial training for farmers, aimed at fostering the adoption of appropriate technology and effective business management, supporting agroforestry farmer independence in production, financing, and marketing. This, in turn, strengthens agroforestry business resilience and long-term prospects for success, both directly and indirectly.